Makna Karikatur Cover Majalah Tempo Edisi September 2019 Studi Semiotika Roland Barthes - Dito Anjasmoro Ningtyas; Haikal Haikal; Yogi Ariska; Eddy Kusnadi (Jurnal Media Penyiaran, 2023)
The tempo magazine is one example of mass media that is much in demand by the public. The contents are interesting, making the magazine still exist today. The widespread use of caricature drawings on uncover ethical magazine covers raises polemic for the public, but also to find caricature meaning on the cover of the September 16, 2019 edition of Tempo, to uncover what the purpose of using pictures or messages to look for is to create a magazine cover, research methods used is qualitative with Roland Barthes theory where Roland Barthes theory discusses semiotics and myths. One of the results of this research is the balanced tempo magazine in conveying the conclusions of a story. It is hoped that the magazine will continue to be consistent in presenting balanced and factual data.